Growth and physiology of the citrange ‘Fepagro C37 Reck’ rootstock innoculated with arbuscular mycorrhizal fungi - Martinello Back, Marina; Fedrizzi, Gabriela; Dutra de Souza, Paulo Vitor (Revista Ceres, 2025)
The use of arbuscular mycorrhizal fungi (AMF) in the production of rootstocks is a strategy to promote faster plant growth. However, this response depends on the symbiont species. The objective of this study was to evaluate the influence of different species of arbuscular mycorrhizal fungus (AMF) on the development and physiology of citrange ‘Fepagro C37 Reck’ rootstock. Four species of AMF were used in the experiment: Scutellospora heterogama, Gigaspora margarita, Glomus etunicatum, and Acaulospora sp., and a control treatment. The experiment was arranged in a randomized blocks design, with 5 treatments, 3 replicates, and 10 plants per plot. Every 15 days, height (cm) and stem diameter (mm) of plants were measured in the nursery. At 330 days, the number of leaves, leaf area (cm²), fresh and dry mass of roots and shoot (g/plant), root and shoot reserve content, and AMF colonization were evaluated. The AMF inoculation promoted an accelerated vegetative growth, resulting in greater height and diameter. The fungi also promoted greater absorption of most of the nutrients and increase in all other parameters evaluated. However, no effect was found on the reserve content of the rootstock. Roots were colonized with moderate presence of arbuscules and low presence of vesicles. AMF, regardless of species, influence the development and physiology of the citrange ‘Fepagro C37 Reck’ rootstock.